THE TYPOLOGY OF PERI – URBAN LAND – USE IN ULEE LHEUE BANDA ACEH CITY - Yasmadi, Herli (Talenta Publisher, 2021)
The suburban area is known as the peri-urban area which is a zone in which there is a mixture of rural and urban land structures. The development of peri-urban areas in Indonesia has spread to almost all cities, which are generally large cities. Urban areas that are not able to balance the needs for residential or commercial space will always take up space in the suburban areas, this is also the case in the Peri Urban Ulee Lheue area of Banda Aceh City. The purpose of this study is to identify how the typology of using land in peri urban areas in Ulee Lheue is to know what typology of land use is happening and how a government program has transformed Ulee Lheue as a strategic location for developing tourism areas and public spaces. The method used in this research is direct field observation method or survey and literature study both theory and supporting documents in the research which then performs data analysis by interpreting the data obtained on the basis of the prevailing theory and policies. The results of this study identify that the typology of land use in peri urban areas in Ulee Lheue is dominated by commercial areas and there are unplanned or informal settlements, besides this research is expected to be able to provide knowledge about the typology of land use in a peri urban area.